Preparation and evaluation of reduction-responsive nano-micelles for miriplatin delivery. Issue 11 (June 2016) - Zhang, Ying; Hu, Dejian; Han, Shangcong; Yan, Guowen; Ma, Chao; Wei, Chen; Yu, Miao; Li, Dongmei; Sun, Yong
A reduction-responsive amphiphilic core-shell micelle for miriplatin delivery was prepared and evaluated. A pyrene-terminated poly(2-(dimethylamino) ethyl acrylate) was synthesized through reversible addition–fragmentation chain transfer polymerization with 4-cyano-4-(ethylthiocarbonothioylthio) pentanoic acid as reversible addition–fragmentation chain transfer reagent and further modified by 2, 2′-dithiodiethanol and 1-pyrenebutyric acid. Self-assembled blank micelles and drug-loaded micelles were obtained by dialysis method, and the particle size was proved to be about 40 nm with narrow dispersity by dynamic laser light scattering. Morphology results showed that blank micelles and drug-loaded micelles were spherical nanoparticles confirmed by transmission electron microscope, and the critical micelle concentration was as low as 6.09 µg/mL via pyrene fluorescence probe method. The reductive sensitivity of disulfide bond in BMs was further verified by changes in particle size, pyrene fluorescence intensity ratio (I338 /I333 ), and morphology after treatment by dithiothreitol. Moreover, drug release rate in vitro of drug-loaded micelles was evaluated and the results suggested that this amphiphilic pyrene-modified poly(2-(dimethylamino) ethyl acrylate) can be used as reduction-triggered controlled release drug delivery carrier for hydrophobic drug.